2009
DOI: 10.3844/ajassp.2009.1440.1447
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Anti-Microbial Effects of Nigella sativa Linn. Seed Extracts Against Clinical Isolates from Skin Wound Infections

Abstract: Problem statement:The developing microbial resistance to the existing anti-microbial agents has become a real challenge and a serious problem facing patients suffering from skin infections. Seeds of Nigella sativa have been used for a long time in folk medicine for the treatment of such infections. Production of new potent agents is urgently needed, especially for hospitals and health centers. Therefore, the anti-microbial effect of aqueous, diethyl ether, chloroform and petroleum ether extracts of the seeds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
1
18
0
4
Order By: Relevance
“…Delayed cutaneous wound healing is a chronic complication in diabetic patients and is caused primarily by hyperglycemia, diminished expression of cytokines, oxidative stress, vascular insufficiency and microbial infections (Lerman et al, 2003;Sivan-Loukianova et al, 2003;Hirsch et al, 2008;Abu-Al-Basal, 2009). Several other diabetic complications like neuropathy, nephropathy, atherosclerosis and foot deformities contribute to the severity of the disease and in the development of chronic wounds in diabetic patients, that might be complicated leading to ulceration, necrosis and amputation (Lerman et al, 2003;Hirsch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Delayed cutaneous wound healing is a chronic complication in diabetic patients and is caused primarily by hyperglycemia, diminished expression of cytokines, oxidative stress, vascular insufficiency and microbial infections (Lerman et al, 2003;Sivan-Loukianova et al, 2003;Hirsch et al, 2008;Abu-Al-Basal, 2009). Several other diabetic complications like neuropathy, nephropathy, atherosclerosis and foot deformities contribute to the severity of the disease and in the development of chronic wounds in diabetic patients, that might be complicated leading to ulceration, necrosis and amputation (Lerman et al, 2003;Hirsch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Skin lightening and skin tightening effects of V. amygdalina extract has not been reported in humans although a study observed skin lightening effects of V. amygdalina in rats whose feed was enhanced with ground V. amygdalina leaves (Abu-Al-Basal, 2009). This study investigated the externally visible effects of V. amygdalina leaf extract on human skin and body energy level.…”
Section: Introductionmentioning
confidence: 99%
“…Nigella sativa seed which has demonstrated numerous antimicrobial anti-oxidant, immunomodulatory and therapeutic effects (Abu-Al-Basalc, 2009;Hanafy and Hatem, 1991;El-Wakil, 2007;Salem, 2005;Siebenhaar et al, 2007) enhanced glucose-induced induced insulin release from rat isolated Islets of langahans (Rchid et al, 2004), which highlights the pivotal role of simple sugars in disease infectivity.…”
Section: Discussionmentioning
confidence: 99%